2021
DOI: 10.1186/s12916-021-02104-3
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and the risk of dementia: is the association explained by shared environmental and genetic factors?

Abstract: Background Frailty has been identified as a risk factor for cognitive impairment and dementia. However, it is not known whether familial factors, such as genetics and shared environmental factors, underlie this association. We analyzed the association between frailty and the risk of dementia in a large twin cohort and examined the role of familial factors in the association. Methods The Rockwood frailty index (FI) based on 44 health deficits was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Frailty has been reported to predict incident dementia [ 58 ]; therefore, the lowest FI values found in our demented persons were expected. Moreover, the men in our cohort were frailer than the women.…”
Section: Discussionmentioning
confidence: 65%
“…Frailty has been reported to predict incident dementia [ 58 ]; therefore, the lowest FI values found in our demented persons were expected. Moreover, the men in our cohort were frailer than the women.…”
Section: Discussionmentioning
confidence: 65%
“…After scanning the titles and abstracts, 79 articles were considered as potentially eligible. After reviewing the bibliography and full-texts, 30 studies met the eligibility criteria, and 20 studies reporting risk estimates were included in the meta-analysis ( Buchman et al, 2007 ; Avila-Funes et al, 2009 , 2012 ; Boyle et al, 2010 ; Gray et al, 2013 ; Solfrizzi et al, 2013 , 2017a , 2017b , 2019 ; Montero-Odasso et al, 2016 ; Feng et al, 2017 ; Rogers et al, 2017 ; Trebbastoni et al, 2017 ; Chen et al, 2018 ; Shimada et al, 2018a , b ; Li et al, 2020 ; Sugimoto et al, 2020 ; Bai et al, 2021 ; Ward et al, 2021 ) cognitive domains ( Boyle et al, 2010 ; Bunce et al, 2019 ; Magnuson et al, 2019 ; Thibeau et al, 2019 ; Gale et al, 2020 ; Paolillo et al, 2020 ; Chen et al, 2021 ; Williams et al, 2021 ), two literature investigated the association between social frailty and cognition ( Tsutsumimoto et al, 2019 ; Huang et al, 2021 ), and one literature investigated the correlation between cognition and frailty status transitions ( Liu et al, 2021 ). The detailed characteristics of studies included in the systematic review and meta-analysis are summarized in Table 1 (for more details see Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven (35%) studies investigated the relationship between cognitive frailty and ACD ( Avila-Funes et al, 2009 ; Montero-Odasso et al, 2016 ; Solfrizzi et al, 2017a , b ; Shimada et al, 2018a , b ; Sugimoto et al, 2020 ) (35%), AD ( Solfrizzi et al, 2017b ) (5%), or cognitive decline ( Montero-Odasso et al, 2016 ) (5%). Six (30%) studies reported the connection between biopsychosocial frailty and ACD ( Rogers et al, 2017 ; Solfrizzi et al, 2019 ; Li et al, 2020 ; Bai et al, 2021 ; Ward et al, 2021 ) (25%) or AD ( Trebbastoni et al, 2017 ; Solfrizzi et al, 2019 ) (10%).…”
Section: Resultsmentioning
confidence: 99%
“…A prospective study from UK Biobank found an increased risk of dementia among participants with pre‐frailty [HR (95% CI): 1.21 (1.04–1.42)] and frailty [HR (95% CI): 1.98 (1.47–2.67)] 4 . Similarly, the Screening Across the Lifespan Twin Study (SALT) showed that a 10% increase in the Rockwood frailty index was associated with a higher risk of dementia, independent of familial factors such as genetic predisposition [HR (95% CI): 1.17 (1.07–1.18) 33 . Frailty is associated with a poor immune system causing a failure to sufficiently respond to acute inflammation 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Screening Across the Lifespan Twin Study (SALT) showed that a 10% increase in the Rockwood frailty index was associated with a higher risk of dementia, independent of familial factors such as genetic predisposition [HR (95% CI): 1.17 (1.07-1.18). 33 Frailty is associated with a poor immune system causing a failure to sufficiently respond to acute inflammation. 34,35 Frailty could increase susceptibility and mortality from pneumonia.…”
Section: Participants' Characteristicsmentioning
confidence: 99%